2020
DOI: 10.1002/batt.201900199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crosslinker Concentration in Poly(Acrylic Acid)‐KOH Gel Electrolyte on Performance of Zinc‐Air Batteries

Abstract: Zinc-air batteries (ZABs) using gel polymer electrolytes suffer from low energy efficiency and poor cyclability. This issue is not only associated with the air electrode, as early failure of the battery is often due to the Zn electrode. Here, the cycle life of ZABs using alkaline poly(acrylic acid) (PAA-KOH) as the electrolyte is shown to vary by changing its crosslinking density. For ZABs using hydrogel electrolytes, understanding the failure mechanism and optimization of the hydrogel composition are key to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…The concentration of KPS was fixed at 1.5 mM, which is consistent with our previous studies. [36,38] Different concentrations of PAA were utilized, i. e., 0.25, 0.5, 1, 1.5 and 2 M, and the KOH concentration was increased accordingly to ensure there was at least 6 M KOH in the PAAÀ KOH network. The samples are denoted as PÀ K1, PÀ K2, PÀ K3, PÀ K4 and PÀ K5, respectively.…”
Section: Synthesis Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of KPS was fixed at 1.5 mM, which is consistent with our previous studies. [36,38] Different concentrations of PAA were utilized, i. e., 0.25, 0.5, 1, 1.5 and 2 M, and the KOH concentration was increased accordingly to ensure there was at least 6 M KOH in the PAAÀ KOH network. The samples are denoted as PÀ K1, PÀ K2, PÀ K3, PÀ K4 and PÀ K5, respectively.…”
Section: Synthesis Of Catalystsmentioning
confidence: 99%
“…Previously, the authors found similar effects for PAA-based gels with varying concentrations of crosslinker. [38] Although ZnO decreases the conductivity of PAAÀ KOH gels, it can help to reduce water activity and Zn corrosion. [47][48][49] Having zincate ions readily available in the electrolyte can also benefit the charging process.…”
Section: Evaluation Of Paaà Koh Gel Electrolytesmentioning
confidence: 99%
“…Hydrogel networks formed from poly-(acrylic acid) (PAA) have the ability to absorb many times their weight in water and are the basis of a class of materials called super absorbent [271] (PAM is also considered a superabsorbent). The degree of crosslinking in the polymer network structure is critical, as it will endows the hydrogel with specific mechanical strength, swelling ratio, and many other properties [163]. As polymeric host material, PAA is chemically and electrochemically stable under highly alkaline environments.…”
Section: Poly-acrylic Acid (Paa) and Sodium Polyacrylate (Pana)mentioning
confidence: 99%
“…The conductivity of PAA-KOH remains stable at high temperatures (360 mScm -1 at 65 • C) because of its high water retention. In battery testing, ZABs with PAA-KOH electrolytes have the potential to outperform batteries with conventional aqueous electrolytes (e.g., 6 M KOH) by reducing interfacial and charge transfer resistance [163]. PAA undergoes a reversible conformational transition (coil-to-globule transition) around pH 5 that is driven by the state of ionization of the carboxylic group.…”
Section: Poly-acrylic Acid (Paa) and Sodium Polyacrylate (Pana)mentioning
confidence: 99%
“…Recently, attempts have been made to modify alkaline electrolytes to enhance the performance of ZABs. Many approaches have been proposed, focusing on the use of inorganic additives, organic solvents (such as surfactants) and polymer gels [ 5 , 17 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%